New Financial Fair Play Requirements in the Context of Global Restrictions - I. V. Solntsev; A. G. Kudryaeva (Финансы: теория и практика, 2023)
The purpose of the paper is to develop recommendations for Russian football clubs aimed at strengthening their financial stability.The subject of the study is the UEFA financial fair play rules and their impact on the financial stability of football clubs.The relevance of the paper is confirmed by the changes taking place in financial regulation of football clubs by the UEFA and the Football Union of Russia (FUR), which are caused by the global crisis and have not yet been studied in the scientific literature, which confirms the novelty of the study. The authors’ method is an analysis of the editions of the UEFA financial fair play rules and RFC licensing rules that have been in effect since 2011, along with any violations and subsequent sanctions. The annual reports of European public football clubs, studies of consulting companies, and academic publications in this field were also considered. This paper helped identify the chronology of financial rules in football and directions for their improvement. The authors conducted a detailed analysis of financial performance of club football in Europe and Russia, taking into account the impact of the pandemic, revealed the main problems and ways to solve them based on best practices.The results of the research included recommendations for conforming to the financial requirements of international federations and FUR as well as ensuring the long-term sustainability of the Russian football industry.